Extranuclear effects of thyroid hormones and analogs during development: An old mechanism with emerging roles - Incerpi, Sandra; Gionfra, Fabio; De Luca, Roberto; Candelotti, Elena; De Vito, Paolo; Percario, Zulema A.; Leone, Stefano; Gnocchi, Davide; Rossi, Miriam; Caruso, Francesco; Scapin, Sergio; Davis, Paul J.; et al. (Frontiers in Endocrinology, 2022)
Thyroid hormones, T3 (triiodothyronine) and T4 (thyroxine), induce a variety of long-term effects on important physiological functions, ranging from development and growth to metabolism regulation, by interacting with specific nuclear or cytosolic receptors. Extranuclear or nongenomic effects of thyroid hormones are also well established: they are mediated by plasma membrane or cytoplasmic receptors, mainly by αvβ3 integrin, and are independent of protein synthesis. A wide variety of nongenomic effects have now been recognized to be elicited through the binding of thyroid hormones to this receptor, which is mainly involved in angiogenesis, as well as in cell cancer proliferation. Several signal transduction pathways are modulated by thyroid hormone binding to αvβ3 integrin: protein kinase C, protein kinase A, Src, or mitogen-activated kinases. Thyroid hormone-activated nongenomic effects are also involved in the regulation of Na+-dependent transport systems, such as glucose uptake, Na+/K+-ATPase, Na+/H+ exchanger, and amino acid transport System A. Of note, the modulation of these transport systems is cell-type and developmental stage-dependent. In particular, dysregulation of Na+/K+-ATPase activity is involved in several pathological situations, from viral infection to cancer. Therefore, this transport system represents a promising pharmacological tool in these pathologies.